Entangling the Quebec Act : transnational contexts, meanings, and legacies in North America and the British empire - Hubert, Ollivier, 1968-; Furstenberg, François (McGill-Queen's studies in early Canada, 2020)
"Beyond redrawing North American borders and establishing a permanent system of governance, the Quebec Act of 1774 fundamentally changed British notions of empire and authority. Although it is understood as a formative moment--indeed part of the "textbook narrative"--in several different national histories, the Quebec Act remains underexamined in all of them. The first sustained examination of the act in nearly thirty years, Entangling the Quebec Act brings together essays by historians from North America and Europe to explore this seminal event using a variety of historical approaches. Focusing on a singular occurence that had major social, legal, revolutionary, and imperial repercussions, the book weaves together perspectives from spatially and conceptually distinct historical fields --legal and cultural, political and religious, and beyond. Collectively, they resituate the Quebec Act in light of Atlantic, American, Canadian, Indigenous, and British Imperial historiographies. A transnational collaboration, Entangling the Quebec Act shows how the interconnectedness of national histories is visible at a single crossing point, illustrating the importance of intertwining methodologies to bring these connections into focus."--